A closer look at astrocyte morphology: Development, heterogeneity, and plasticity at astrocyte leaflets. (June 2022) - Torres-Ceja, Beatriz; Olsen, Michelle L.
Abstract: Astrocytes represent an abundant type of glial cell involved in nearly every aspect of central nervous system (CNS) function, including synapse formation and maturation, ion and neurotransmitter homeostasis, blood–brain barrier maintenance, as well as neuronal metabolic support. These various functions are enabled by the morphological complexity that astrocytes adopt. Recent experimental advances in genetic and viral labeling, lineage tracing, and live- and ultrastructural imaging of miniscule astrocytic sub-compartments reveal a complex morphological heterogeneity that is based on the origin, local function, and environmental context in which astrocytes reside. In this minireview, we highlight recent findings that reveal the plastic nature of astrocytes in the healthy brain, particularly at the synapse, and emerging technologies that have advanced our understanding of these morphologically complex cells.